Participation in real-world laboratories in a new light?! Closing the gap between co-creative and deliberative participation. - Sonnberger, Marco; Lindner, Doris (Oekom, 2021)
Sustainability-oriented real-world laboratories involve the co-design and co-creation of knowledge, based on a trans-disciplinary cooperation between actors from different socialworlds – academia, the administration, business, civil society – each endowed with specific interests, resources and world-views. Sustainability-oriented real-world laboratories claim to be a means of inclusive participation in the co-creative shaping of solutions for socioecological issues and exploring pathways to sustainability. In the literature dealing with sustainability-oriented real-world laboratories, participation is thus mainly understood as active involvement by civil society, change agents and citizens in processes of experimentation and the implementation of solutions. We call this co-creative participation. However, participation in talk-based opinion formation and decision-making processes – we call this deliberative participation – is hardly discussed in the respective literature. In this paper, we argue that co-creative and deliberative participation are two forms of participation which can be conceptualized differently but which are both relevant for successful experimentation in sustainability-oriented real-world laboratories and are mainly intertwined in practice. We propose an ideal-typical conceptual framework for participation in sustainability-oriented real-world laboratories that combines co-creative and deliberative participation. The aim is to contribute to a systematization of, and rationale for, different forms of participation in real-world laboratories.

Nachhaltigkeitsorientierte Reallabore beinhalten Ko-Design und Ko-Kreation von Wissen, basierend auf einer transdisziplinären Zusammenarbeit von Akteuren aus verschiedenen sozialen Welten – Wissenschaft, Verwaltung, Wirtschaft, Zivilgesellschaft – jeweils ausgestattet mit spezifischen Interessen, Ressourcen und Weltanschauungen. Nachhaltigkeitsorientierte Reallabore sollen ein Mittel zur inklusiven Partizipation an der ko-kreativen Lösungsfindung für sozialökologische Probleme sein. In der aktuellen Literatur zu nachhaltigkeitsorientierten Reallaboren wird Partizipation zumeist als aktive Beteiligung von Zivilgesellschaft, Pionieren des Wandels und Bürgern in realweltlichen Prozessen des Experimentierens und der Implementation von Problemlösungen verstanden. Die Autoren bezeichnen dies als ko-kreative Partizipation. Formen dialogbasierter Meinungsbildung und Entscheidungsfindung (deliberative Partizipation) finden in der einschlägigen Literatur dagegen kaum Beachtung. In diesem Beitrag wird argumentiert, dass ko-kreative und deliberative Partizipation zwei unterschiedlich verfasste Formen von Partizipation sind, die jedoch beide von Relevanz für den Erfolg eines nachhaltigkeitsorientierten Reallabors sind. Die Autoren schlagen einen idealtypischen konzeptionellen Rahmen vor, der ko-kreative und deliberative Partizipationsformen kombiniert und so eine Systematisierung und Begründung unterschiedlicher Partizipationsformen in Reallaboren liefert.
Partizipation in Reallaboren in neuem Licht?! Ein Ansatz, die Lücke zwischen ko-kreativer und deliberativer Partizipation zu schließen.
Keywords: Reallabor; Partizipation; Nachhaltigkeit; Kooperationsmodell; Akteur; Sozialökologie; Experiment; Problemlösung; Transdisziplinarität; Realexperiment